Pengaruh Struktur Modal, Pertumbuhan Penjualan Dan Keputusan Investasi Terhadap Nilai Perusahaan - Arianti, Baiq Fitri; Yatiningrum, Riya (Gorontalo Accounting Journal, 2022)
The purpose of research is to empirically prove the influence of capital structure, sales growth and investment decisions on corporate value on mining sector companies listed on the Indonesia Stock Exchange in 2016-2020. The sampling method used is a purposive sampling method and obtained by 17 companies that are the objects of research. The study used regression analysis of panel data, using Eviews version 9. Based on the results of the analysis tested, showed that (1) jointly (simultaneously) capital structure, sales growth and investment decisions have an effect on firm value, (2) capital structure have a negative and significant effect on the value of the company, (3) sales growth have no effect on the value of the company, and (4) investment decisions have no effect the on value of the company.